PENGGUNAAN PETROGENOL 800 L UNTUK MENGENDALIKAN HAMA LALAT BUAH (BACTROCERA SP) PADA TANAMAN CABAI - Patty, John Alfred (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to provide practical skills and knowledge to the community regarding the use of 800 L petrogenol to control fruit fly pests (Bactrocera sp) on chili plants. The target of implementing this activity is the community of Waimital Village, Kairatu District, West Seram Regency. Community participation in this activity was very good. This is related to the problem faced by chilies, namely the attack of fruit flies (Bactrocera sp) which causes losses, both in quantity and quality. There was a positive response from the extension participants to continue using 800 L petrogenol in order to minimize control costs and increase farmers' knowledge in chili cultivation. Therefore, farmers really need information regarding the use of 800 L petrogenol to control pests in chili plantations